2008
DOI: 10.1161/circgenetics.108.782730
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Peripheral-Blood Gene Expression With the Extent of Coronary Artery Stenosis

Abstract: Background-The molecular pathophysiology of coronary artery disease (CAD) includes cytokine release and a localized inflammatory response within the vessel wall. The extent to which CAD and its severity is reflected by gene expression in circulating cells is unknown. Key Words: gene expression Ⅲ coronary disease Ⅲ blood, peripheral Ⅲ atherosclerosis Ⅲ leukocytes Ⅲ polymerase chain reaction Ⅲ stenosis C oronary artery disease (CAD) and sequelae of atherosclerotic disease such as stroke and myocardial infarction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
132
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 168 publications
(143 citation statements)
references
References 33 publications
7
132
0
2
Order By: Relevance
“…According to Horwitz, et al 50) expression profiles of blood cells may be a more sensitive screening test for cardiac allograft rejection than endomyocardial biopsy. Peripheral blood gene expression is also correlated with the extent of coronary heart disease 51) and chronic heart failure, 52) and could be used to differentiate patients with ischemic end-stage heart failure from patients with asymptomatic heart dysfunction. 11) Recently, Devaux, et al 53) identified a set of 3 potential biomarkers (VEGFB, THBS1 and PGF) of left ventricular dysfunction in blood cells from patients after MI.…”
Section: Discussionmentioning
confidence: 99%
“…According to Horwitz, et al 50) expression profiles of blood cells may be a more sensitive screening test for cardiac allograft rejection than endomyocardial biopsy. Peripheral blood gene expression is also correlated with the extent of coronary heart disease 51) and chronic heart failure, 52) and could be used to differentiate patients with ischemic end-stage heart failure from patients with asymptomatic heart dysfunction. 11) Recently, Devaux, et al 53) identified a set of 3 potential biomarkers (VEGFB, THBS1 and PGF) of left ventricular dysfunction in blood cells from patients after MI.…”
Section: Discussionmentioning
confidence: 99%
“…The method may be developed to identify subjects at very high risk of ischemic events. Online address: http://www.molmed.org doi: 10.2119/molmed.2011.00479 tients, healthy controls and patients with thoracic aortic aneurysm, as well as patients differing in their extent of coronary artery disease (6)(7)(8)(9)(10). Other studies have examined diseased tissue biopsied from the site of disease, with a similar aim of identifying disease-specific gene expression (11)(12)(13)(14)(15).…”
Section: Prediction Of Ischemic Events On the Basis Of Transcriptomicmentioning
confidence: 99%
“…These last 2 findings are consistent with the confirmed ability of the GES to identify not only the likelihood of obstructive CAD but also the burden of the disease. 36 Fourth, while clinical outcomes were monitored for at least 30 days, it may be possible that adverse cardiac events occurred after this follow-up period. Previous evaluation of patients from the COMPASS and PREDICT validity studies have shown a very low rate of major adverse cardiovascular events over 6 and 12 months followup, respectively, among patients with low GES.…”
Section: Discussionmentioning
confidence: 99%